Remote physical function testing in older adults: a mixed methods study exploring test reliability, feasibility, and perceptions of participants and assessors - Jackson J. Fyfe; Fernando Sousa; Kimberley Watson-Mackie; Paul Jansons; David Scott; Robin M. Daly (PLoS ONE, 2025)
Impaired physical function is linked to poor health outcomes in older adults. Low-cost, remote strategies for monitoring physical function could enable timely interventions, improving health and reducing the need for support services. This study aimed to evaluate the feasibility, reliability, and perceptions of remotely assessing physical function in older adults at home. Nineteen community-dwelling older adults (68 ± 5 years; 68% female) participated in three videoconferencing sessions with trained assessors, one week apart. Participants completed nine physical function tests [standing balance test battery, single-leg balance, four-square step test (FSST), gait speed (2.44 m and 4 m, both usual and fastest pace), five-times sit-to-stand (5-STS), 30-second STS (30-STS)]. Semi-structured interviews with participants and assessors explored feasibility and acceptability. Test-retest reliability was assessed using intraclass correlation coefficients (ICCs) and Bland-Altman plots, and interview data were analysed thematically. All participants completed assessments without adverse events. Test-retest reliability ranged from poor (ICC < 0.5 for single-leg balance) to good (ICC 0.75–0.9 for 5-STS, 30-STS, gait, and FSST), improving with repeated testing. Participants identified challenges with device setup and physical demands of preparing their home. Assessors noted participant understanding as a barrier. Both groups recognised support from others during testing as a key enabler. Older adults can safely and feasibly perform physical function tests remotely. Familiarisation improves reliability and reducing technical and physical demands can enhance implementation. Support from others at home may be important for successful remote testing.